A novel targeted delivery system for drug-resistant hepatocellular carcinoma therapy. Issue 32 (11th August 2020) - Xiao, Li; Hou, Yang; He, Huimin; Cheng, Sinan; Hou, Yifan; Jin, Huijuan; Song, Xigui; Nie, Guochao; Hou, Yingchun
Abstract : HCSP4-Lipo-DOX-miR101 is a novel and efficient approach for HCC targeted therapy with MDR inhibition in vitro and in vivo . Abstract : Hepatocellular carcinoma (HCC) is a severe malignant disease threatening human life. Current chemotherapy methods usually result in poor prognosis with low treatment efficacy and high side effects because of weak targeting specificity and fast acquisition of multidrug resistance (MDR). HCSP4 is a 12-aa peptide previously identified to specifically and sensitively bind to HCC cells and tissues. In this study, a novel class of HCC-targeting doxorubicin (DOX) delivery system, named HCSP4-Lipo-DOX-miR101, was synthesized and investigated for anticancer activity. HCSP4-Lipo-DOX-miR101 exhibited specific HCC targeting characteristics and satisfactory anticancer potency against HepG2 and HepG2/ADR cells, particularly HepG2/ADR cells. Moreover, the expression levels of genes closely related to membrane transport and cancer growth were significantly suppressed. This finding suggests that HCSP4-Lipo-DOX-miR101 can cause DOX-resistant HCC cell death and growth inhibition based on the targeting of MDR-related genes by miR-101. In conclusion, the findings of this study suggest that HCSP4-Lipo-DOX-miR101 may serve as a promising novel targeted delivery system for improving the therapeutic efficiency of drug-resistant hepatocellular carcinoma.